MODAV-MP2020: contribuições para o aprimoramento de mestrados profissionais - Pereira, Júlio César (2020)
This study is inspired by Paulo Freire, who states that to be a good educator you must have the conviction that change is possible. Although necessary, this assertion is resisted in the area of Education, which hinders change, justified by low investments, disqualification of professionals, low salaries, lack of conditions for teaching, among other problems. To overcome resistance, this study seeks to advance by proposing alternatives in the field of Educational Assessment, focusing on self-assessment practices as a way to intervene, and change, the daily life with a view to improving the training project. Self-assessment, in the specific case of this study of a Professional Graduate Program - stricto sensu -, also seeks to unveil this project, identifying the logical-evolutionary sequence of the actions that go on and weaving a web of processes and relationships: student and citizen profile being forged? What are we training for? How are we forming? In this sense, the general objective of this work is to continue a self- assessment model (MODAV-MP), whose first stage of implementation took place between the years 2015 to 2017. The purpose of this work was to implement the second stage of the model (2018 to 2020) that is now identified by MODAV-MP2020, its phases and its dynamic action in motion, as well as the idea of evaluating itself taking into account a set of three assumptions: 1) the participation of those involved in the evaluation planning; 2) legitimation and 3) the dissemination of knowledge. In this new stage, authors were sought to support a self-assessment model based on the participatory / emancipatory assessment paradigm - Freire (1979, 1997); Schön (1992); Guba & Lincoln (2011); Ferreira (2019) among others. The methodology maintained the same four types of evaluation as the original project. They are: 1) ex ante (diagnosis): focuses on the analysis of the points that highlight the weaknesses and potentialities, with emphasis on the use of the selection process as a source of information (registration for the process, letter of intent, pre-research project , the written test and interview; 2) ex post (process): it aims to analyze the conditions, difficulties, facilities, in short, the intervening factors that contribute to the change process, with emphasis on the application of the Academic Information (QIA); 3) ex post (product): it aims to identify the changes effectively built in the school routine that can be attributed to the dynamics of training work, with emphasis on the exploration of the products (dissertations and multipapers) developed by graduate students (as) and 4) ex post (effect): it aims to identify the possible marks left by training work, with emphasis on listening to graduates. The results point to the importance of the decision-making process, by management, based on scientific data, which guide the next cycle of MODAV-MP. In the final considerations, reflections are proposed that explore aspects of the inseparability between Education and change inspired by the studies proposed by Paulo Freire.